PATH-16. EVALUATION OF SEX-BASED DIFFERENCES IN CLINICAL OUTCOMES AND TUMOR GENOMICS IN PATIENTS WITH NEWLY DIAGNOSED IDH-WILDTYPE GLIOBLASTOMA RECEIVING CHEMORADIATION. (12th November 2021) - Shi, Diana; Lim-Fat, Mary Jane; Nassar, Amin; Woods, Jared; Youssef, Gilbert; Pisano, William; Whorral, Sydney; Allen, Marie; Cagney, Daniel; Tanguturi, Shyam; Haas-Kogan, Daphne; Aizer, Ayal; et al.
Abstract: BACKGROUND: We evaluated sex-based differences in clinical outcomes and tumor genomics in patients with newly-diagnosed GBM. METHODS: We reviewed 665 IDH-wild type GBM patients with Karnofsky Performance Status (KPS) ≥60 treated at our institution from 2010-2019 including; 585 patients with targeted exome sequencing of 447 cancer associated genes (OncoPanel). Deleterious mutations were defined as homozygous deletions or loss of function mutations of known tumor suppressors (as reported in TCGA, ≥ 3 times in the COSMIC database, or predicted as "damaging" in SIFT and/or "probably damaging" in Polyphen 2) or known oncogenic mutations in proto-oncogenes (reported in TCGA or ≥ 3 times in COSMIC). RESULTS: There were 384 (57.7%) males and 281 (42.3%) females. Median OS was 22.5 months for females and 19.3 months for males (hazard ratio [HR] 0.81, 95% CI 1.03-1.48, p = 0.02). On multivariable analysis adjusted for age, KPS ≥90, extent of resection, and MGMT methylation status, female sex (adjusted hazard ratio 0.78, 95% CI [0.64-0.95], p = 0.015) was associated with improved OS. Superior OS in females was observed in MGMT-unmethylated patients (HR 0.69, 95% CI [0.54-0.90], p = 0.005) but not MGMT-methylated patients. Thirteen genes were deleteriously altered in ≥5% of our cohort: CDK4 (12.1% male vs. 7.8% female), CDKN2A (46.5% vs. 45.7%), CDKN2B (41.8% vs. 43.3%), EGFR (34.7% vs. 40.0%, MTAP (18.2% vs. 18.8%), NF1 (11.5% vs. 9.4%), PTEN (28.2% vs. 29.8%), TP53 (28.2% vs. 30.2%), RB1 (5.6% vs. 6.5%), MDM4 (6.2% vs. 5.7%), ATM (5.9% vs. 3.7%), MDM2 (7.4% vs. 4.1%), PIK3R1 (6.2% vs. 4.1%). There were no differences in frequency of mutations in these individual genes between males and females (χ 2 [1, N=585] = 0.05-2.86, p = 0.09-0.86). CONCLUSIONS: Female sex is associated with improved survival. We did not identify sex-based differences in deleterious genomic alterations amongst commonly altered genes in GBM.